Investigation of Asymmetric Dimethylarginine, Adiponectin, Zn, and Cu Levels in Obese Subjects - (:unkn) unknown (SPRINGER, 2019)
Obesity plays a role in the pathogenesis of various diseases such as especially inflammatory process and metabolic syndrome. Herein, we aimed to determine levels of adiponectin, asymmetric dimethylarginine, zinc, and copper in obese as well as the evaluation of the relationship among them because we could not find any study evaluated together that these parameters affected by each other in the same patient group. The white adipose tissue is considered to be the most significant energy reservoir and secretes a large number of biologically active adipokines. Adiponectin from these adipokines draws attention due to antidiabetic and antiatherogenic effects and is expected to be a new therapeutic tool for diabetes and metabolic syndrome. Individuals were created obese and control subjects. Obese individuals were identified by body mass index (BMI). Adiponectin levels in serum were measured by ELISA test, asymmetric dimethylarginine was analyzed by using HPLC method, and Cu and Zn levels were determined with the help of absorption spectroscopy. Adiponectin was significantly lower (p<0.001) in obese subjects whereas copper was significantly higher (p<0.001) compared to the control group. However, no statistical differences were observed between asymmetric dimethylarginine and Zn levels. Besides, adiponectin amounts were inversely related to copper and BMI. Furthermore, there was a positive correlation between copper and BMI in the subjects. Our findings have shown a significant relation between adiponectin and Cu levels in obese subjects. Also, adiponectin has an essential role in the etiopathogenesis of obesity and adiponectin administration, and Cu restriction might be important in the issue of obesity.
Keywords: Asymmetric dimethylarginine; Adiponectin; Obesity; ADIPOSE-SPECIFIC PROTEIN; TRACHEOBRONCHIAL AIRWAYS; POMEGRANATE EXTRACT; REALISTIC MODEL; MAGNETIC-FIELD; NITRIC-OXIDE; WEIGHT-LOSS; PLASMA; COPPER; SIMULATION